The Muslim Afterlife Reward and Punishment Beliefs and Expectations Profiles - Al-Issa, Riyad; Krauss, Steven; Roslan, Samsilah; Abdullah, Haslinda; Mundher Oraibi, Bha-Aldan (Indonesian Journal of Islam and Muslim Societies, 2025)
Literature from the cognitive and cultural evolutionary sciences of religion indicates that afterlife reward and punishment beliefs increase prosociality. Although Muslims are among the strongest adherents in afterlife reward and punishment belief, there is evidence that there are low levels of prosociality in these societies. This study explores this paradox. Because previous studies have mostly relied on variable-centered approaches to analysis, it is difficult to understand how different afterlife beliefs and expectations together affect Muslims. Using a person-centered approach, the current study employed Latent Profile Analysis to understand how Islamic afterlife reward and punishment beliefs and expectations interact with each other, and what profiles result from this interaction. The study further explored the relationships between the resulting profiles with religiosity, prosociality (integrity, rule breaking ability, self-control), death attitude (death anxiety, and acceptance), and future orientation. The study used data collected from Jordanian (n= 605) university students. The results indicate that profiles with high levels of afterlife reward and punishment beliefs and afterlife hope expectations have a positive association with religiosity, prosociality and death attitude in both samples, while profiles with high levels of afterlife fear expectation, temporary afterlife punishment expectation, and compulsory temporary afterlife punishment belief have a negative association with religiosity, prosociality and death attitude. The profiles that show the best performance constitute only 23 percent of the Jordanian sample. The study results confirm the existence of a unique phenomenon in which supernatural punishment beliefs have a negative effect on prosocial behavior resulting from belief in temporary punishment in the afterlife.